Lactococcus lactis M4, a potential host for the expression of heterologous proteins - Nanyan, Noreen; Hooi, Wei Yeng; Baradaran, Ali; Mohamad, Rosfarizan; Sieo, Chin Chin; Md Illias, Rosli; Yusoff, Khatijah; Abdul Rahim, Raha (BioMed Central, 2011)
BACKGROUND: Many plasmid-harbouring strains of Lactococcus lactis have been isolated from milk and other sources. Plasmids of Lactococcus have been shown to harbour antibiotic resistance genes and those that express some important proteins. The generally regarded as safe (GRAS) status of L. lactis also makes it an attractive host for the production of proteins that are beneficial in numerous applications such as the production of biopharmaceutical and nutraceutical. In the present work, strains of L. lactis were isolated from cow's milk, plasmids were isolated and characterised and one of the strains was identified as a potential new lactococcal host for the expression of heterologous proteins. RESULTS: Several bacterial strains were isolated from cow's milk and eight of those were identified as Lactococcus lactis by 16S rRNA sequence analysis. Antibiotic susceptibility tests that were carried out showed that 50% of the isolates had almost identical antibiotic resistance patterns compared to the control strains MG1363 and ATCC 11454. Plasmid profiling results indicated the lack of low molecular weight plasmids for strain M4. Competent L. lactis M4 and MG1363 were prepared and electrotransformed with several lactococcal plasmids such as pMG36e, pAR1411, pAJ01 and pMG36e-GFP. Plasmid isolation and RE analyses showed the presence of these plasmids in both M4 and the control strain after several generations, indicating the ability of M4 to maintain heterologous plasmids. SDS-PAGE and Western blot analyses also confirmed the presence of GFP, demonstrating the potential of heterologous protein expression in M4. CONCLUSIONS: Based on the 16S rRNA gene molecular analysis, eight Gram-positive cocci milk isolates were identified as L. lactis subsp. lactis. One of the strains, L. lactis M4 was able to maintain transformed low molecular weight plasmid vectors and expressed the GFP gene. This strain has the potential to be developed into a new lactococcal host for the expression of heterologous proteins.